Towards sustainable businesses in Latin America: The role of worker's Dark Triad personality traits - Afshar, Asghar (2023)
Having sustainable businesses becomes priority for many Latin American countries these years. Socially responsible behaviors (SRBs) of employees in the workplace plays important roles in making businesses more sustainability oriented. The main aims of this research to identify those employees, which involve less in two types of SRBs: societal behaviors and sustainability-oriented behaviors at the workplace by considering their Dark Triad personality traits. By using survey-based data from 550 workers in Peru and Ecuador, we found a negative relationship between workers Dark Triad personality traits (Machiavilism and Psychopathy) and their socially responsible behaviors in the workplace. Furthermore, our results show that workers with higher level of Machiavilism and psychopathy has lower level of environmental concerns, which in turn reduce their intentions to involve in socially responsible behaviors in the workplace. Our study advances sustainable business research in Latin America by providing workers Machiavellianism and Psychopathy as a novel predictor of socially responsible behaviors of employees at the workplace.